Transfer Pricing dalam Perspektif Global: Analisis Pengaruh Tax Haven dan Fluktuasi Nilai Tukar - Syabilla Purnama; Nurul Aisyah Rachmawati (Jurnal Akuntansi dan Keuangan, 2025)
This study aims to determine the effect of tax havens and exchange rates on corporate transfer pricing decisions, with company size and leverage as control variables. This study uses a binary logistic test. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2019. The research period was chosen to minimize bias in the results due to the effects of the COVID-19 pandemic. The study population was 192 companies, but only 84 met the research criteria. The results of this study indicate that the variable of tax haven utilization has no effect on transfer pricing, and the variable of exchange rates has no impact on transfer pricing.